Role of Stock Market Performance and Exchange Rate Volatility in the Inflow of Foreign Direct Investment: An Evidence from Pakistan - Rukhsana Rasheed; Mazhar Nadeem Ishaq; Muhammad Fahad Malik (iRASD Journal of Management, 2022)
The purpose of this study was to evaluate the role of macroeconomic variables i.e., stock market performance and exchange rate fluctuations on Foreign Direct Investment (FDI) for Pakistan. The required data was collected for the period of 1996 to 2020 from the World Bank and State Bank of Pakistan. In data analysis, the unit-root tests were performed to decide whether a time-series is stationary or not. An ARDL is constructed to achieve the results of this study. The results of this study provided the evidences that stock market performance and trade openness have positively and significantly linked with FDI. Whereas real GDP growth rate and exchange rates have negative effects on FDI. It is recommended that the trade policies should be devised in such a manner that these policies should promote exports. Furthermore, policies that ensure stable stock market performance could be an important factor for bringing FDI to Pakistan. However, FDI seems to be ineffective from the changes in the rate of inflation.